Pengaruh Modal Kerja dan Jam Kerja Terhadap Pendapatan Pedagang Kaki Lima (PKL) di Jalan Sentot Ali Basa Kelurahan Payo Selincah Kota Jambi - Oktavia, Nurfeny; Suherman; Rika Neldawaty; Abd Halim (Fakultas Hukum dan Ekonomi Bisnis, 2025)
This study aims to analyze and describe the social and economic characteristics of street vendors, and to analyze the influence of working capital and working hours on street vendor income along Jalan Sentot Ali Basa, Payo Selincah Village, Jambi City. The method used in this study is descriptive quantitative, with data collection using questionnaires, interviews, and documentation to strengthen the results. The data used are primary data, and the analysis techniques used are multiple linear regression analysis and classical assumption testing, assisted by the SPSS version 25.0 analysis tool. The results of this study indicate that the working capital variable has a positive and significant influence on the income of street vendors on Sentot Ali Basa Street, Payo Selincah Village, Jambi City. Meanwhile, the working hours variable does not have a significant influence on the income of street vendors on Sentot Ali Basa Street, Payo Selincah Village, Jambi City.